Triple Immunotherapy Overcomes Immune Evasion by Tumor in a Melanoma Mouse Model - Jallad, Mary-Ann N.; Jurjus, Abdo R.; Rahal, Elias A.; Abdelnoor, Alexander M. (Frontiers in Oncology, 2020)
Three agents, Monophosphoryl Lipid A (MPLA), Cytotoxic T-Lymphocyte Associated Antigen-4 Antibodies (CTLA-4ab) and Methyl Tryptophan (MT) were used in this study. MPLA is a relatively non-toxic derivative of bacterial lipopolysaccharide that previously was shown to have antitumor properties and is a potent adjuvant that is used in cancer vaccines. CTLA-4ab blocks CTLA-4 that acts as an immunosuppressive agent following the induction of an immune response and MT blocks the tumor enhancing property of indolamine dioxygenase (IDO). All three agents (MPLA, CTLA-4ab and MT) were tested each alone, and in combinations to see if they caused adverse effects in female C57BL/6 mice. No adverse effects were detected. C57BL/6 female mice each were then given one million B16F10 melanoma cells and divided into groups, each group consisted of 12 to 13 mice. Two groups served as controls and the other groups received one of the three agents or different combinations of the three agents. Survival analysis indicated that the groups receiving dual or triple therapies had prolonged survival compared to the controls. However, the group receiving triple therapy (MPLA, CTLA-4ab and MT) was the only group to show statistically significant increase in survival compared to the controls. Tumor size progression analysis came in accordance with the survival outcome. The group receiving the triple therapy showed statistically significant lower tumor sizes compared to all the other groups throughout the whole monitoring period. Finally, flow cytometry used to analyze immune cell populations in the tumor mass indicated that the triple immune therapy = was capable of significantly enhancing the natural killer cells counts as well as the CD3+CD4+/Treg and CD3+CD8+/Treg ratios possibly enhancing the anti-tumorigenic environment. It can be concluded that the triple therapy thwarted melanoma progression in mice.